Návrh rekonstrukce žst. Krahulov - Tumpach, Jan (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Cílem diplomové práce je rekonstrukce železniční stanice Krahulov tak, aby umožňovala přístup pro osoby s omezenou schopností pohybu a orientace. V souvislosti se změnou nástupišť byla vyřešena úprava kolejiště a odvodnění při zachování napojení na přilehlé vlečky.

The aim of the diploma thesis is the reconstruction of the railway station Krahulov in aim to fulfil the requirements for people with limited mobility. In connection with the change of the platform was resolved adjustment rails and drainage while maintaining a connection to an adjacent sidings.
Design of Reconstruction of the Krahulov Railway Station
Keywords: Železniční stanice; rekonstrukce; nástupiště; odvodnění; výhybky; geometrické parametry koleje.; Railway station; reconstruction; platforms; drainage; switches and crossings; track alignment.